Young Children with a Bucket-Handle Tear to the Discoid Lateral Meniscus Successfully Treated Using Arthroscopic Saucerization and Repair: Two Case Reports - Yu-Hsiang Liao; Chun-Ho Chen; Chii-Jeng Lin; Wei-Ren Su; Chia-Lung Shih; Chen-Hao Chiang (Medicina, 2022)
Observations of a symptomatic discoid lateral meniscus in young children are infrequent. The objective of this report was to demonstrate the use of arthroscopic saucerization and repair for treating a bucket-handle tear of a lateral discoid meniscus in two young children. Two young children (a 28-month-old girl and a 5-year-old boy) presented with a bucket-handle tear of the complete type lateral discoid meniscus. Both patients received arthroscopic saucerization and repair. A full knee extension under a long leg cast was applied for one month after surgery. The two patients were able to achieve a full range of motion of their operated knees without limping or presenting an antalgic gait at the third month after surgery. Both patients and their parents felt satisfied with the treatment at the 2- and 3-year follow-ups, respectively. Our results demonstrated that arthroscopic saucerization and repair seems to be an effective treatment for bucket-handle tears of the lateral discoid meniscus in young children—even those younger than 3 years old. We reported the youngest case (a 28-month-old girl) in comparison with the findings from a literature review.